Reasons for not undergoing cervical cancer screening: perspectives from women and health care providers in Addis Ababa: a qualitative study - Mohammed, Ebrahim; Kaba, Mirgissa; Taye, Girma; Assefa, Mathewos; Jemal, Ahmedin; Addissie, Adamu (Frontiers in Oncology, 2025)
BackgroundCervical cancer is a major public health problem in low-income countries, including Ethiopia. Various pieces of evidence show that the uptake of cervical cancer screening is low in Ethiopia. The reasons for this low uptake of cervical cancer screening have not been well documented.ObjectiveThe aim of this study is to explore the reasons for not taking up cervical cancer screening and gather the perspectives of women and healthcare providers in Addis Ababa, Ethiopia.MethodsAdult women and healthcare providers participated in the study. Eleven focus group discussions were conducted with women from the community. A total of 18 key Informant interviews were conducted with healthcare professionals who providing cervical cancer screening services and family health team leaders. Interviews and discussions were audio recorded, transcribed, and coded. We used MAXQDA software v.20 for data reduction to facilitate thematic analysis and interpretation.ResultsEleven focus group discussions and 18 key informant interviews were conducted. In this study, individual-level barriers, such as low knowledge of cervical cancer and screening, feeling healthy, fear of the screening procedure and results, fear of not being cured, fear of divorce, stigma and discrimination, preference for female healthcare providers, and spousal disapproval or resistance, were identified as the main reasons for the low uptake of screening. Community-level barriers such as perceiving cervical cancer as a deadly disease; misconceptions, such as screening causing infertility, and the absence of open discussion, were also found to contribute to low screening uptake.Conclusion and recommendationsKnowledge about cervical cancer and screening was found to be inadequate. Individual and community-level socio-cultural barriers were identified as reasons for the low uptake of screening. Therefore, it is crucial to conduct behavioral change and communication activities at both the individual and community levels to increase knowledge of cervical cancer and screening, reduce sociocultural barriers, and improve the uptake of cervical cancer screening.